2016
DOI: 10.1007/s12526-016-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent variation in density of corallivorous snails (Coralliophila spp.) at Curaçao, southern Caribbean

Abstract: Snails of the genus Coralliophila (Muricidae: Coralliophilinae) are common in the Caribbean as corallivores that feed on a large range of host species. The present study concerns the distribution of two Coralliophila snails, C. caribaea and C. galea, at 5-m and 10-m depths at Curaçao (southern Caribbean), as associates of the common scleractinians Orbicella annularis and Pseudodiploria strigosa. Coralliophila galea was abundant on both host species, while C. caribaea was represented only by a single individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…All encountered host associations for C. galea were also found in Curaçao [12]. Orbicella annularis was by far the most common host of Coralliophila galea, which also agrees with results found on Curaçao [94]. Studies in other Caribbean localities also reported this association as common [95,96].…”
Section: Discussionsupporting
confidence: 87%
“…All encountered host associations for C. galea were also found in Curaçao [12]. Orbicella annularis was by far the most common host of Coralliophila galea, which also agrees with results found on Curaçao [94]. Studies in other Caribbean localities also reported this association as common [95,96].…”
Section: Discussionsupporting
confidence: 87%
“…Most of the host species associations for Coralliophila galea and C. caribaea found in the present study have been previously recorded (Miller, 1981;Brawley and Adey, 1982;Hayes, 1990a;Bruckner et al, 1997;Del Monaco et al, 2010;Potkamp et al, 2017). Feeding of C. galea on Orbicella annularis was found to be infrequent around 1970 (Robertson, 1970;Ott and Lewis, 1972), but later clearly impacted reef communities (Brawley and Adey, 1982;Knowlton et al, 1988Knowlton et al, , 1990Hayes, 1990a;Bruckner et al, 1997;Baums et al, 2003b).…”
Section: Discussionsupporting
confidence: 73%
“…Paradoxically, in the classification proposed by Darling et al (2012) , Orbicella annularis (formerly known as Montastraea annularis ) ( Budd et al, 2012 ) is placed in the stress-tolerant category. There is evidence, however, indicating that the vital rates of this coral are sensitive to environmental stressors such as increased water temperature ( Edmunds & Elahi, 2007 ; Hernández-Pacheco, Hernández-Delgado & Sabat, 2011 ) and is one of the most susceptible Caribbean corals to corallivorous snails ( Potkamp, Vermeij & Hoeksema, 2017a , 2017b ). It is, also, susceptible to coral diseases ( Bruckner & Bruckner, 2006 ; Weil, Urreiztieta & Garzón-Ferreira, 2002 ; Weil, Cróquer & Urreiztieta, 2009 ) and is classified as “endangered” by the IUCN list ( Carpenter et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%